RESEARCH ABOUT STRATEGY IN THE BRAZILIAN PUBLIC SECTOR: SCIENTIFIC PRODUCTION EVALUATION IN THE PERIOD OF 2007 – 2011 - Ferreira, Vicente da Rocha Soares; Najberg, Estela; Porto, Rafael Barreiros; Sousa, Marcos de Moraes; Barbosa, Nelson Bezerra (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
The corporate strategy has been widely investigated in the private sector but in the public sector has not received similar attention, despite its importance for the management of both sectors. Existing investigations can be sparse and may include other areas of administration. The objective of this paper is to describe the evolution of Strategy Research in the Public Sector. A systematization and a brief review of scientific literature on strategy were done in the public sector in Brazil. This is a bibliometric research with data from the database SCIELO Brazil, in the period of 2007-2011. The selected items were published in journals A1, A2, B1, B2 and B3 of the Administration field, which resulted in the study of 35 papers. The analysis points to: there is little research in Strategy in the Public Sector and, this sector has not yet used the instrumental provided by Strategy field.